A study of the efficacy of stellate ganglion blocks in complex regional pain syndromes of the upper body - Rashmi Datta; Jyotsna Agrawal; Amit Sharma; Vikram Singh Rathore; Shivesh Datta (Wolters Kluwer Medknow Publications, 2017)
Background and Aims: The effect of stellate ganglion blocks (SGBs) was examined in complex regional pain syndromes (CRPS) of the upper body. Material and Methods: A total of 287 SGB were given to patients with documented CRPS on medications. Spontaneous and provoked pain assessment was done with numeric pain rating scale (NPRS). The Disabilities of the Arm, Shoulder and Hand (DASH) questionnaire and range of motion (ROM) was recorded before and after each blockade. Difference between a 15-point "global rating of change" scale determined the minimal clinically important difference of the DASH score. Results: The overall mean pain reduction was 73.2% (r = 0.83, P < 0.001) considering spontaneous and 55.8% (r = 0.77, P < 0.001) on provoked pain. Mean DASH score decreased from 53 (range 36-63; P = 0.14) to 10.4 (range 10-49.2; P = 0.005). The sensitivity to change was 6.9 for spontaneous and 4.9 for provoked pain. Increase in ipsilateral limb temperature has a good correlation with Horner's syndrome (HS) and sympathetic blockade. Minor, self-limiting complications, such as hoarseness, dysphagia, local hematoma, and ipsilateral brachial plexus block occurred in 11.5%. A rare complication of contralateral HS was documented. One patient developed a small pneumothorax, but it did not require intervention. Conclusions: SGB are relatively safe and effective management in patients with neuropathic conditions already on pharmacotherapy. Serial blocks attained an average reduction in pain by >3 NPRS points from the baseline for both spontaneous and provoked pain with a decrease in mean DASH score and improvement in ROM.